Facile enzymatic synthesis of sugar 1-phosphates as substrates for phosphorylases using anomeric kinases. (12th January 2015) - Liu, Yuan; Nishimoto, Mamoru; Kitaoka, Motomitsu
Graphical abstract: Highlights: We describe one-pot enzymatic synthesis of three sugar 1-phosphates. Anomeric kinases were used in the presence of an ATP-regeneration system. These sugar 1-phosphates were available as crystals of particular salts. These sugar 1-phosphates are donor substrates for phosphorylases. Abstract: Three sugar 1-phosphates that are donor substrates for phosphorylases were produced at the gram scale from phosphoenolpyruvic acid and the corresponding sugars by the combined action of pyruvate kinase and the corresponding anomeric kinases in good yields. These sugar 1-phosphates were purified through two electrodialysis steps. α-d -Galactose 1-phosphate was finally isolated as crystals of dipotassium salts. α-d -Mannose 1-phosphate and 2-acetamido-2-deoxy-α-d -glucose 1-phosphate were isolated as crystals of bis(cyclohexylammonium) salts.